2003
DOI: 10.1155/2003/103682
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Practice Patterns in the Treatment of Methicillin‐Resistant Staphylococcus aureus Skin and Soft Tissue Infections at Three Canadian Tertiary Care Centres

Abstract: Considerable variation exists in treatment patterns for MRSA infections. Improvements in the initiation of therapy and the use of IV-to-oral switch therapy may improve care and reduce the duration of hospitalization for MRSA SSTIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…In total the charts of 89 patients treated with vancomycin IV for an MRSA infection were reviewed for the study (23). The demographic and clinical characteristics of patients are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total the charts of 89 patients treated with vancomycin IV for an MRSA infection were reviewed for the study (23). The demographic and clinical characteristics of patients are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Details regarding the methodology and results of the chart review have been previously reported (23). In summary, the charts of all patients admitted to one of three tertiary care teaching hospitals (Vancouver Hospital and Health Sciences Centre, Vancouver, British Columbia; The University Health Network, Toronto, Ontario; and Hôpital Maisonneuve-Rosemont, Montreal, Quebec) between January 1, 1997 and August 31, 2000 and treated with vancomycin IV for an active MRSA infection were reviewed.…”
Section: Chart Review Of Mrsa Treatment Patternsmentioning
confidence: 99%
“…Guidelines for IV to oral switch therapy in patients with community-acquired pneumonia are included in national guidelines published by the British Thoracic Society [10] and the Infectious Diseases Society of America/American Thoracic Society [11]; the latter additionally includes criteria for ED. The actual or potential benefits of ES and ED programmes were demonstrated in numerous studies enrolling patients with various types of infections including those caused by bacteria and fungi [7,9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25]29,33]. Indeed, in children with pyelonephritis early IV to oral switch was deemed noninferior to IV therapy only, thereby providing further evidence to support this intervention [34].…”
Section: Benefits Of Es and Ed Programmesmentioning
confidence: 99%
“…Numerous criteria were evaluated in studies evaluating ES and ED programmes in patients with various types of infections including lower respiratory tract infections, urinary tract infections, SSTIs, intraabdominal infections (Table 1) [7,9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Most programmes assessed ES and ED eligibility 2-4 days following initiation of IV antibiotic therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation